Assessing Stakeholder Adaptive Capacity to Salmon Aquaculture in Norway - Tiller, Rachel; Richards, Russell; Salgado, Hugo; Strand, Hilleveli; Moe, Espen; Ellis, John (Consilience, 2014)
Determining the socio-ecological effects of increased aquaculture/farmed fish production through the granting of new licenses to the industry around the island group of Frøya in Trøndelag, Norway, is explored in this paper. This is investigated from a stakeholder perspective, assessing the adaptive capacity of the given community in each region through workshops combining Scenario Analysis, Systems Thinking and Bayesian Belief Network, developing conceptual frameworks and influence diagrams visualizing the perceived effects of the industry on the given stakeholder system. This adaptive capacity is critical to explore before a de facto industry expansion. This is because there can be context-specific adaptation policies and measures that can be pursued that reduce a given stakeholder group´s vulnerability to negative consequences of industry expansion. Policy makers’ a priori knowledge of these variables can lessen conflicts that may arise as a result of stakeholder discontent with top-down approaches to fisheries management. It can also bring a legitimizing aspect to the political process leading to integrated coastal zone management (IZCM) in the region for affected stakeholder groups, possibly lessening simmering conflicts.